Using neuro-linguistic programming and transactional analysis tools to measure the English proficiency of foreign language learners - Almosa, Abdulrahman (Research Journal in Advanced Humanities, 2023)
Various methods are used to evaluate the English skills of non-native learners. Two approaches within cognitive science have garnered attention lately due to their potential usefulness in learning a foreign language and improving an individual's interpersonal and communicative skills. They include Transactional Analysis (TA) and Neuro-Linguistic Programming (NLP). Self-improvement, psycho-education, and language teaching extensively use these psychological methods for assessing and evaluating students' behaviour. Communication skills, such as consciousness, fearlessness, and others, are essential to teach English in the classroom and can be trained through methods like NLP and TA. This study focused on measuring different variables that underpin proficiency in a foreign language. The six variables measured in this study include speaking, listening, reading, and writing skills. Grammar and vocabulary proficiency were also measured. The measuring instrument was the NLP and TA tools, and the method adopted for the study is an experimental approach. Two hundred high school students participated in both the pretest and posttest. Both the researcher and some selected teachers administered the tests. The findings of the study affirm that the participants generally performed better across the skill sets for proficiency in the posttest, more than what is seen in the pretest. This indicates that the tools help measure and facilitate learning different FL proficiency skills. The study further revealed that the students performed better during the posttest in the TA test than in the NLP test. The findings also indicated that the students performed better in speaking and listening skills in both the posttests of NLP and TA tests. It is thus concluded that TA and NLP are critical tools to measure students' progress in certain areas of FL learning.